Isolated and On Guard: Preparing Neonatal Intensive Care Unit Families for Life with Hydrocephalus - Dorner, Rebecca A.; Boss, Renee D.; Burton, Vera J.; Raja, Katherine; Robinson, Shenandoah; Lemmon, Monica E. (American Journal of Perinatology, 2021)
Objective This study was aimed to characterize the parent experience of caring for a child with posthemorrhagic hydrocephalus and to describe parent preferences for counseling in the neonatal period and beyond.Study Design This was a qualitative interview study. Parents of infants born preterm with posthemorrhagic hydrocephalus completed semistructured interviews. Data were analyzed using a content analysis approach.Results Thematic saturation was reached on parent communication preferences after 10 interviews. Parent experiences of infant hydrocephalus broadly fell into two time periods, the neonatal intensive care unit (NICU) and after NICU discharge. The themes of uncertainty, isolation, hypervigilance, and the need for advocacy were common to each phase.Conclusion Parents expressed interest in the development of tiered NICU counseling tools that would provide evidence-based and family-centric information to (1) initiate connections with community and peer resources and (2) combat the isolation and hypervigilance that characterized their family experience of living with hydrocephalus.Key Points
Keywords: neonatal intensive care unit; hydrocephalus; parents; qualitative research